Anti-CD20 Disrupts Meningeal B-Cell Aggregates in a Model of Secondary Progressive Multiple Sclerosis. Issue 3 (May 2021) - Roodselaar, Jay; Zhou, Yifan; Leppert, David; Hauser, Anja E.; Urich, Eduard; Anthony, Daniel C.
Abstract : Objective: Therapies targeting B cells have been used in the clinic for multiple sclerosis (MS). In patients with relapsing MS, anti-CD20 therapy often suppresses relapse activity; yet, their effect on disease progression has been disappointing. Most anti-CD20 therapeutic antibodies are type I, but within the unique microenvironment of the brain, type II antibodies may be more beneficial, as type II antibodies exhibit reduced complement-dependent cytotoxicity and they have an increased capacity to induce direct cell death that is independent of the host immune response. Methods: We compared the effect of type I with type II anti-CD20 therapy in a new rodent model of secondary progressive MS (SPMS), which recapitulates the principal histopathologic features of MS including meningeal B-cell aggregates. Focal MS-like lesions were induced by injecting heat-killed Mycobacterium tuberculosis into the piriform cortex of MOG-immunized mice. Groups of mice were treated with anti-CD20 antibodies (type I [rituxumab, 10 mg/kg] or type II [GA101, 10 mg/kg]) 4 weeks after lesion initiation, and outcomes were evaluated by immunohistochemistry. Results: Anti-CD20 therapy decreased the extent of glial activation, significantly decreased the number of B and T lymphocytes in the lesion, and resulted in disruption of the meningeal aggregates. Moreover, at the given dose, the type II anti-CD20 therapy was more efficacious than the type I and also protected against neuronal death. Conclusions: These results indicate that anti-CD20 may be an effective therapy for SPMS with B-cell aggregates and that the elimination of CD20 + B cells alone is sufficient to cause disruption of aggregates in the brain.